The Emerging Roles of Extracellular Vesicles As Communication Vehicles within the Tumor Microenvironment and Beyond - Sullivan, Ryan; Maresh, Grace; Zhang, Xin; Salomon, Carlos; Hooper, John; Margolin, David; Li, Li (Frontiers in Endocrinology, 2017)
Tumors evolve in complex and dynamic microenvironments which they rely on for sustained growth, invasion, and metastasis. Within this space, tumor cells and non-malignant cells are in frequent communication. One specific mode of communication that has gained recent attention is the release of extracellular vesicles. Extracellular vesicles are lipid bilayer-bound vehicles that are released from the cell membrane and carry nucleic acids, proteins, and lipids to neighboring or distant cells. Extracellular vesicles have been demonstrated to influence a multitude of processes that aid in tumor progression including cellular proliferation, angiogenesis, migration, invasion, metastasis, immunoediting, and drug resistance. The ubiquitous involvement of extracellular vesicles on cancer progression makes them very suitable targets for novel therapeutics. Furthermore, they are being studied as specific markers for cancer diagnostics, prognosis, and even as chemotherapy drug-delivery systems. This review focuses on the most recent advances in extracellular vesicle knowledge, some current and potential problems with their use, and some proposed solutions to consider for the future.